The Proliferation of Regional Regulation Cancellation in Indonesia - Abdul Kadir Jaelani; Muhammad Jihadul Hayat (Journal of Human Rights, Culture and Legal System, 2022)
The purpose of constitutional amendments is to grant the Supreme Court the authority to review laws and regulations in accordance with the law. However, the arrangement did not function optimally due to the government's persistent assumption of the authority to cancel Regional Regulations. In an era of regional autonomy, the purpose of this study is to examine the implementation of the ranking of laws and regulations regarding the repeal of regional legal products. This is a normative legal study utilizing secondary data. The results demonstrated that the concept of implementing the ranking of laws and regulations on the repeal of regional legal products during the era of regional autonomy was not carried out in accordance with the constitution and should have been limited while it was still in the form of draft regional regulations.